Biological Activity of Flavonoids and Rare Sesquiterpene Lactones Isolated From Centaurea ragusina L. - Grienke, Ulrike; Radić Brkanac, Sandra; Vujčić, Valerija; Urban, Ernst; Ivanković, Siniša; Stojković, Ranko; Rollinger, Judith M.; Kralj, Juran; Brozovic, Anamaria; Radić Stojković, Marijana (Frontiers in Pharmacology, 2018)
The endemic Croatian species Centaurea ragusina L., like other species from the genus Centaurea, has been traditionally used in Croatia as an antibacterial agent and for the treatment of gastrointestinal and urogenital disorders. In several chromatographic steps, three flavonoids and three sesquiterpene lactones were isolated and identified from the most active fractions of the ethanol extract. Two sesquiterpene lactones, one for which we created the trivial name ragusinin, and hemistepsin A are here reported for the first time as constituents of the genus Centaurea. All six compounds were screened for their effect on several tumor and one normal cell lines. Among them, the ragusinin showed the best bioactivity and high specificity to affect tumor murine SCCVII, human HeLa and Caco-2 cell lines, but not the viability of normal V79 fibroblasts. Due to these characteristics the action of ragusinin was investigated in more detail. Since DNA is the primary target for many drugs with antibacterial and anticancer activity, we studied its interaction with ragusinin. Rather moderate binding affinity to DNA excluded it as the primary target of ragusinin. Due to the possibility of sesquiterpene lactone (STL) interaction with glutathione (GSH), the ubiquitous peptide that traps reactive compounds and other xenobiotics to prevent damage to vital proteins and nucleic acids, its role in deactivation of ragusinin was evaluated. Addition of the GSH precursor N-acetyl-cysteine potentiated the viability of HeLa cells, while the addition of GSH inhibitor L-buthionine sulfoximine decreased it. Moreover, pre-treatment of HeLa cells with the inhibitor of glutathione-S-transferase decreased their viability indicating the detoxifying role of GSH in ragusinin treated cells. Cell death, derived by an accumulation of cells in a G2 phase of cell cycle, was shown to be independent of poly (ADP-ribose) polymerase and caspase-3 cleavage pointing towards an alternative cell death pathway.